Distinctive Risk Factors and Phenotype of Younger Patients With Resistant Hypertension: Age Is Relevant. Issue 5 (May 2017) - Ghazi, Lama; Oparil, Suzanne; Calhoun, David A.; Lin, Chee Paul; Dudenbostel, Tanja
Abstract : Resistant hypertension, defined as blood pressure >140/90 mm Hg despite using ≥3 antihypertensive medications, is a well-recognized clinical entity. Patients with resistant hypertension are at an increased risk of cardiovascular disease compared with those with more easily controlled hypertension. Coronary heart disease mortality rates of younger adults are stagnating or on the rise. The purpose of our study was to characterize the phenotype and risk factors of younger patients with resistant hypertension, given the dearth of data on cardiovascular risk profile in this cohort. We conducted a cross-sectional analysis with predefined age groups of a large, ethnically diverse cohort of 2170 patients referred to the Hypertension Clinic at the University of Alabama at Birmingham. Patients (n=2068) met the inclusion criteria and were classified by age groups, that is, ⩽40 years (12.7% of total cohort), 41 to 55 years (32.1%), 56 to 70 years (36.1%), and ≥71 years (19.1%). Patients aged ⩽40 years compared with those aged ≥71 years had significantly earlier onset of hypertension (24.7±7.4 versus 55.0±14.1 years; P <0.0001), higher rates of obesity (53.4% versus 26.9%; P <0.0001), and significantly higher levels of plasma aldosterone (11.3±9.8 versus 8.9±7.4 ng/dL; P =0.005), plasma renin activity (4.9±10.2 versus 2.5±5.0 ng/mL per hour; P =0.001), 24-hour urinary aldosterone (13.4±10.0 versus 8.2±6.2 µg/24 h; P <0.0001), and sodium excretion (195.9±92.0 versus 146.8±67.1 mEq/24 h; P <0.0001). Among patients with resistant hypertension, younger individuals have a distinct phenotype characterized by overlapping risk factors and comorbidities, including obesity, high aldosterone, and high dietary sodium intake compared with elderly. Abstract : Supplemental Digital Content is available in the text.